Evaluation of the therapeutic effects of the topical and systemic forms of Honokiol in 5-fluorouracil-induced oral mucositis model in rats - Ayse Ozcan Kucuk; Aydın Keskinruzgar; Zehra Bozdag (Scientific Reports)
Abstract This study aimed to evaluate the effects of honokiol on 5-florourasil (5-FU) induced oral mucositis (OM) in rats. A total of 24 female Wistar Albino rats were injected with 5‑FU on day 1, 3 and 5. A superficial scratch was linearly created on the right buccal mucosa on days 3 and 5. The animals were randomly divided into control, vehicle, topical honokiol and systemic honokiol groups and sacrificed on the day 10 after the first 5-FU application. Blood and tissue sampling were analysed for total antioxidant status (TAS) levels, total oxidant status (TOS) levels plus histopathological evaluations. When the systemic and topical groups and vehicle group compared to control group, no statistically significant difference was found histopathological scores. (p = 1.000, p = 0.264, p = 1.000, respectively). There were no significance differences in histopathological scores between systemic and topical groups (p = 1.000), or between systemic and vehicle groups (p = 0.139). A statistically significant difference was observed in the histopathologic analysis between the topical and vehicle groups, (p = 0.006). There were no differences in TAS and TOS between the groups. The authors found no beneficial effect of systemic or topical honokiol on healing 5‑FU‑induced OM. To confirm its effects on OM, further studies are required with different study designs.